Odd Price: Harga, Psikologi dan Perilaku Konsumen dalam Purchase Decision Making - Kartika Imasari Tjiptodjojo (Universitas Kristen Maranatha, 2012)
Price is one important component in marketing as well as in creating of customer value. Determination of an appropriate pricing strategy will not only affect consumers' perception of the level, but will bring the consumers to the point of purchase. Odd Price is one of the company's strategies to create the impression in the minds of consumer’s low price. This strategy is considered quite successful in influencing consumer psychology in deciding to buy the product or service offered by the company.